2016
DOI: 10.5222/tmcd.2015.149
|View full text |Cite
|
Sign up to set email alerts
|

Demodex folliculorum Infestation in a Patient with Hodgkin's Lymphoma: A Case Report

Abstract: SUMMARY Demodex folliculorum Infestation in a Patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Another study has reported that Demodex infestation can be more common in diabetic patients as the disease may increase the possibility of an immunosupressed state (Akdeniz et al, 2002). Disorders compromising the immune system such as cancer, chemotherapy, chronic renal failure, and organ transplantation have been reported to potentially cause D. folliculorum infestation (Bastemir et al, 2015). Similarly, Zeytun and Olmez (2017) found that immunosuppression can significantly increase Demodex density and that COAD patients have higher rates of Demodex infestation than control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has reported that Demodex infestation can be more common in diabetic patients as the disease may increase the possibility of an immunosupressed state (Akdeniz et al, 2002). Disorders compromising the immune system such as cancer, chemotherapy, chronic renal failure, and organ transplantation have been reported to potentially cause D. folliculorum infestation (Bastemir et al, 2015). Similarly, Zeytun and Olmez (2017) found that immunosuppression can significantly increase Demodex density and that COAD patients have higher rates of Demodex infestation than control subjects.…”
Section: Discussionmentioning
confidence: 99%